K63-linked ubiquitination regulates RIPK1 kinase activity to prevent cell death during embryogenesis and inflammation - Yong Tang (Nature Portfolio, 2019)
Receptor-interacting protein kinase 1 (RIPK1) is a critical regulator of cell death but its regulation is unclear. Here, the authors report that RIPK1 kinase activity is regulated by ubiquitination.